Kajian Etis Teologis Penyalahgunaan Mengonsumsi Minuman Alkohol di Kalangan Pemuda di Jemaat GMIM Maranatha Molompar Satu Wilayah Tombatu Timur - Wuwung, Hilkia Mitchel Israel; Rumengan, Arthur R. (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
This article discusses the Theological Ethical Study of the Abuse of Consuming Alcoholic Beverages Among Youth in the GMIM Maranatha Molompar Satu Congregation in the East Tombatu Region. This study aims to describe the factors that cause youth to be addicted to consuming alcoholic beverages. Through this research, it was found that there are several factors that motivate youth to consume alcohol excessively, namely as a way to overcome stress or pressure from everyday life, even because of social factors and curiosity that causes consuming alcohol. It also examines the ethical theological meaning of young people who are addicted to alcohol.